Pelatihan Membuat Banten Pejati bagi Masyarakat Desa Wisata Spiritual Suranadi Lombok Barat - Desak Putu Saridewi; I Made Sudarma; Ide Kade Suparta; I Nengah Putra Kariana (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Community Service Activities in the form of training to make banten pejati, aims to develop human resources as support for spiritual tourism in Suranadi village, West Lombok Regency. This activity is motivated by the absence of traders who provide banten pejati in the village, even though as a spiritual tourism area it is an attraction for tourists who want to pray. The availability of banten pejati sellers in spiritual tourism areas can also make it easy for tourists, especially those from outside the region. Based on these observations, to accommodate and develop Human Resources in Suranadi village, a training program for making banten pejati in simple packaging is needed without losing its philosophical meaning. Data collection methods used in this training program are observation, interviews, and documentation. The training begins with strengthening the understanding of the philosophy of banten pejati, then continues with demonstrations and practice in groups. The results of the evaluation showed that the participants were enthusiastic about participating in the training and showed their respective creativity in the form of the ability to make tetuasan, the design of banten pejati which was minimalist, practical, economical, and fast (in a short time). Participants are expected to be able to build the skills gained from this training in an ongoing and independent manner.